'We Are the Monitors Now': Experiential Knowledge, Transcorporeality and Environmental Justice. (June 2016) - Scott, Dayna Nadine
Residents of pollution hotspots often take on projects in 'citizen science', or popularepidemiology, in an effort to marshal the data that can prove their experience of the pollution to the relevant authorities. Sometimes these tactics, such as pollution logs or bucket brigades, take advantage of residents' spatially ordered and finely honed experiential and sensory knowledge of the places they inhabit. But putting that knowledge into conversation with law requires them to mobilize a new, 'foreign' set of tools, primarily oriented to the observation, measurement and sampling of pollution according to conventional scientific standards. Here, I employ qualitative empirical methods in two case studies of communities 'downwind' of Canada's contested tar sands region to demonstrate that the knowledge that is crucial to these citizen science strategies is not only local, situated and experiential in origin but also collectively generated and held. I draw on the notion of transcorporeality, emanating from feminist theory of the body, to demonstrate that the knowledge offered to law through these efforts often represents a fluid merger of experiential and conventional ways of knowing, posing a productive challenge to the strictly positive notions of science and evidence dominant in legal proceedings.